Trichoscopy of scalp dysesthesia - Rakowska, Adriana; Olszewska, Małgorzata; Rudnicka, Lidia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Scalp dysesthesia is characterized by localized pruritus, burning sensations or even pain. Aim : To describe characteristic trichoscopic features of scalp dysesthesia. Material and methods: The study was a retrospective analysis (2010–2016) of 9 patients (8 females and 1 male; median age: 52 years; range: 38–66 years). A total of 61 trichoscopic images were analyzed by two independent evaluators. Results: In all cases, oval or round areas covered with short hairs: broom hairs (77%; 7/9), block hairs (88%; 8/9), short hairs with trichorrhexis nodosa (78%; 7/9) were found. In 4 of 9 cases these areas were circumscribed by brownish linear discoloration. Background features included: areas lacking hair shafts (44%; 4/9) covered by wavy-shaped scaling, whitish areas with prominent perifollicular yellow discoloration and cloud vessels arranged around follicular openings and around empty follicles (33%, 3/9); focal brownish discoloration with darker wavy lines (78%; 7/9). Conclusions : Trichoscopy can be helpful in establishing the diagnosis of scalp dysesthesia – broom hairs, block hairs and short hairs with trichorrhexis nodosa covering the alopecia patch, uniform in length, can be considered as characteristic for this condition.